2011
DOI: 10.1109/tevc.2010.2087026
|View full text |Cite
|
Sign up to set email alerts
|

An Inflationary Differential Evolution Algorithm for Space Trajectory Optimization

Abstract: In this paper we define a discrete dynamical system that governs the evolution of a population of agents. From the dynamical system, a variant of Differential Evolution is derived. It is then demonstrated that, under some assumptions on the differential mutation strategy and on the local structure of the objective function, the proposed dynamical system has fixed points towards which it converges with probability one for an infinite number of generations. This property is used to derive an algorithm that perfo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
102
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(104 citation statements)
references
References 22 publications
0
102
0
2
Order By: Relevance
“…Remark 2: Even though the general conditions for global convergence of evolutionary algorithms are established in [48], it cannot be analytically shown that DE meets these conditions [49] and converges to the global solution of (16). Moreover, in [48], no specific algorithm that meets these conditions is proposed.…”
Section: B Differential Evolution Based Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…Remark 2: Even though the general conditions for global convergence of evolutionary algorithms are established in [48], it cannot be analytically shown that DE meets these conditions [49] and converges to the global solution of (16). Moreover, in [48], no specific algorithm that meets these conditions is proposed.…”
Section: B Differential Evolution Based Estimationmentioning
confidence: 99%
“…Moreover, in [48], no specific algorithm that meets these conditions is proposed. Although in [49], a variation of DE is proposed, it is indicated in [49] that this new approach also does not guarantee the global convergence of the DE algorithm. Nevertheless, by appropriately selecting the DE parameters, in our extensive simulations, we have observed the proposed DE estimator to always converge to the true values of timing and frequency offsets as described in Sections IV-C and VI-A.…”
Section: B Differential Evolution Based Estimationmentioning
confidence: 99%
“…evolutionary computing (EC) and optimization has since emerged as a means for dealing with highly constrained mission profiles for primarily interplanetary trajectories. Evolutionary methods utilized have included genetic algorithms [2,3], particle swarm optimization [4], monotonic basin hopping [5], simulated annealing [6], and differential evolution [7]. To a lesser extent, EC methods have also been leveraged for in-orbit trajectory planning about planets [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Olds and Kluever [17] also focused on interplanetary trajectory design, analyzing the effects of altered DE tuning parameters of four interplanetary trajectory test problems. A derivative of DE was proposed by Vasile et al [7] that added a localized population restart to DE reminiscent of monotonic basin hopping. Vasile and Locatelli [18] also applied elements of search similar to DE in a domain decomposition search approach to interplanetary trajectory design with success.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting algorithm has been demonstrated to out-perform both DE and MBH on some difficult space trajectory design problems, for instance those where the search space has a (multi) funnel-like structure. 7 The main features of the IDEA algorithm are reported in depth by Vasile et al;…”
mentioning
confidence: 99%